Health Improvements Have Been More Rapid and Widespread in China than in India: A Comparative Analysis of Health and Socioeconomic Trends from 1960 to 2011 - Gopal K. Singh, PhD; Jihong Liu, ScD (Global Health and Education Projects, Inc., 2016)
Objectives We examined differences between China and India in key health and socioeconomic indicators, including life expectancy, infant and child mortality, non-communicable disease mortality from cancer, cardiovascular diseases (CVD), and diabetes, Human Development Index, Gender Inequality Index, material living conditions, and health expenditure. Methods Data on health and social indicators came from various World Health Organization and United Nations databases on global health and development statistics, including the GLOBOCAN cancer database. Mortality trends were modeled by log-linear regression, and differences in rates and relative risks were tested for statistical significance. Results Although both countries have made marked improvements, India lags behind China on several key health indicators. Differential rates of mortality decline during 1960-2009 have led to a widening health gap between China and India. In 2009 the infant mortality rate in India was 50 deaths per 1,000 live births, 3 times greater than the rate for China. Sixty-six out of 1,000 Indian children died before reaching their 5th birthday, compared with 19 children in China. China's life expectancy is 9 years longer than India's. Life expectancy at birth in India increased from 42 years in 1960 to 65 years in 2009, while life expectancy in China increased from 47 years in 1960 to 74 years in 2009. Major health concerns for China include high rates of stomach, liver, and lung cancer, CVD, and smoking prevalence. Globally, India ranked 90th and China 102nd in life satisfaction. Conclusions and Public Health Implications: India's less favorable health profile compared to China is largely attributable to its higher rates of mortality from communicable diseases and maternal and perinatal conditions. Further health gains can be achieved by reducing social inequality, greater investments in human development and health services, and by prevention and control of chronic-disease risks such as hypertension, smoking, obesity, and physical inactivity. Key Words: China • India • Health status • Life expectancy • Infant and child mortality • Non-communicable diseases • Cancer • Health risks • Human development • Social inequality.